2020
DOI: 10.3201/eid2612.191450
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic New World Relapsing Fever Borrelia in a Myotis Bat, Eastern China, 2015

Abstract: Yanase T. Characterization of genome segments 2, 3 and 6 of epizootic hemorrhagic disease virus strains isolated in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…For Borrelia-positive Rh. pusillus (bat ID: XN788), sequence query showed that the 8 housekeeping genes were exactly the same as ST927, which was previously reported by our team in a Myotis ricketti bat from Shandong Province, China [14]. For Borrelia-positive My.…”
Section: Mlst Analysissupporting
confidence: 70%
See 4 more Smart Citations
“…For Borrelia-positive Rh. pusillus (bat ID: XN788), sequence query showed that the 8 housekeeping genes were exactly the same as ST927, which was previously reported by our team in a Myotis ricketti bat from Shandong Province, China [14]. For Borrelia-positive My.…”
Section: Mlst Analysissupporting
confidence: 70%
“…davidii (bat ID: XN888), the 8 loci of MLST were all novel alleles, and the 8 loci were submitted to the Borrelia MLST database and novel allele numbers were assigned: clpA (303), clpX (263), nifS (238), pepX (267), pyrG (278), recG (294), rplB (256), and uvrA (270), and sequence typing was assigned as ST938. Phylogenetic analysis based on the concatenated 8 housekeeping genes (4,776 bp, in the order of clpA - clpX - nifS - pepX - pyrG - recG - rplB - uvrA ) revealed that the Borrelia species found in bats from this study clustered with a group of human pathogenic relapsing fever Borrelia spirochetes, and were most related to Candidatus Borrelia fainii, which was recently identified in a febrile patient, bats and soft ticks from Zambia [ 13 ], as well as in a bat from Shandong Province, China [ 14 ] ( Fig 3 ). Phylogenetic trees based on each of the 8 loci of relapsing fever Borrelia were shown in S1 – S8 Figs.…”
Section: Resultsmentioning
confidence: 64%
See 3 more Smart Citations